PRACTICAL ASPECTS OF THE PRIMARY SCHOOL TEACHER PROFESSIONAL TRAINING UNDER THE CONDITIONS OF EUROPEAN INTEGRATION - Miier, Tetiana; Bondarenko, Hennadiy (Educological discourse, 2020)
The article deals with issues related to primary school teachers` professional training in the context of European integration. In particular, the transformational processes in European education of managerial, organizational and content direction are summarized; the main ideas of modernizing the content and process of primary school teachers` professional training in the countries of Europe are pointed out. The attention is drawn to the fact that in European countries the primary school teachers` professional training is considered, first of all, as a way of providing society with a highly-qualified competitive staff, who serve as leaders in the global economic space; secondly, as a means of building a single European space and dimension of education; thirdly, as a process that provides a qualitative transition from instructive to constructive teaching methods focused on active creative and independent activity of students, in particular, the fulfillment of research tasks, solving problem situations, participating in discussions, performing creative works, etc. Also, the article considers some aspects of the content modernization of primary school teachers` professional training in the context of European integration, which are realized by the teaching staff of Primary Education Department of Pedagogical Institute of Borys Grinchenko Kyiv University. This is an analytical lecture and seminar work upon European educational experience; an introduction of active teaching methods, a usage of modern strategies, means of organizing students’ educational and cognitive activity, etc. The process of primary school teachers` professional training in the context of European integration is aimed at providing a wide range of knowledge, abilities, skills, professional competences, gaining practical experience, forming the ability and motivation for continuous professional development in the system of life-long education, realization of cognitive activity, creativity, purposefulness in actions.